"Sudah Selesai" (Τετέλεσται): Finalitas Korban Kristus dan Implikasinya terhadap Pemaknaan Ulang Korban dalam Praktik Iman Kristen Kontemporer - Wennar Wennar; Yanto Paulus Hermanto (Jurnal Lentera Nusantara, 2026)
The concept of sacrifice is one of the central themes in biblical theology and undergoes significant development from the Old Testament to the New Testament. Although the doctrine of the finality of Christ’s sacrifice has long been recognized as a foundational element of Christian theology, various contemporary church practices still tend to interpret sacrifice within legalistic and transactional frameworks, resulting in an incomplete understanding of the theological significance of Christ’s finished work. In response to this issue, this study aims to analyze the sacrificial system in the Old Testament, explain its fulfillment in the person and work of Jesus Christ, and examine the theological implications of Jesus’ declaration, “It is finished” (Tetelestai) in John 19:30, for contemporary Christian faith and practice. This research employs a qualitative library-based approach through exegetical analysis of biblical texts related to sacrifice and a review of relevant theological literature. The findings indicate that the Old Testament sacrificial system was typological in nature and found its definitive fulfillment in Christ’s sacrifice, which was offered once for all (ephapax). The declaration Tetelestai affirms the finality of Christ’s redemptive work, the fulfillment of Messianic prophecy, and His victory over sin and death. The novelty of this study lies in its integration of biblical analysis, systematic theology, and pastoral reflection to explain the transformation of the concept of sacrifice from a ritual means of atonement to a response of faith expressed through a life of dedication, service, and worship. This study concludes that Christ’s sacrifice brought the need for ritual atoning sacrifices to an end while simultaneously providing the foundation for a Christian life characterized by gratitude, devotion, and obedience rooted in the grace of God.AbstrakKonsep korban merupakan salah satu tema sentral dalam teologi Alkitab yang mengalami perkembangan signifikan dari Perjanjian Lama hingga Perjanjian Baru. Meskipun doktrin mengenai finalitas korban Kristus telah menjadi bagian penting dalam teologi Kristen, berbagai praktik kehidupan gereja kontemporer masih menunjukkan kecenderungan memahami pengorbanan dalam kerangka legalistik dan transaksional, sehingga makna teologis karya Kristus yang telah tuntas sering kali tidak dipahami secara utuh. Berangkat dari permasalahan tersebut, penelitian ini bertujuan menganalisis sistem korban dalam Perjanjian Lama, menjelaskan penggenapannya dalam pribadi dan karya Yesus Kristus, serta mengkaji implikasi teologis seruan “Sudah selesai” (Tetelestai) dalam Yohanes 19:30 bagi kehidupan iman Kristen kontemporer. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi pustaka melalui analisis eksegetis terhadap teks-teks Alkitab yang berkaitan dengan tema korban serta kajian literatur teologis yang relevan. Hasil penelitian menunjukkan bahwa sistem korban Perjanjian Lama bersifat tipologis dan menemukan penggenapan definitif dalam korban Kristus yang bersifat sekali untuk selamanya (ephapax). Seruan Tetelestai menegaskan finalitas karya penebusan, penggenapan nubuat mesianik, dan kemenangan Kristus atas dosa serta maut. Kebaruan penelitian ini terletak pada upaya mengintegrasikan analisis biblika, teologi sistematis, dan refleksi pastoral untuk menjelaskan transformasi makna korban dari sarana penebusan ritual menuju respons iman yang diwujudkan melalui persembahan hidup, pelayanan, dan penyembahan. Penelitian ini menyimpulkan bahwa korban Kristus mengakhiri kebutuhan akan korban penebusan ritual, tetapi sekaligus menjadi dasar bagi kehidupan Kristen yang berorientasi pada syukur, pengabdian, dan ketaatan yang berakar pada anugerah Allah.